Analisis Oposisi Makna “Catatan Buat Emak” dalam Trilogi Novel Ronggeng Dukuh Paruk Karya Ahmad Tohari - Mahbub, Moh. Tarojjil; Sumarlam, Sumarlam (Kajian Linguistik dan Sastra, 2025)
This research is a type of qualitative descriptive study that uses the "listening" method with the "note-taking" technique to collect data. The aim of this study is to describe the lexical aspects of antonymy in the first part of the trilogy novel Ronggeng Dukuh Paruk “Catatan Buat Emak” by Ahmad Tohari, which was published in 1982. The object of this research is antonymy (opposition of meaning). The data in this research consists of utterances or dialogues between characters in the Ronggeng Dukuh Paruk novel, which contain oppositions of meaning along with their context. The source of the data for this study is the Ronggeng Dukuh Paruk novel by Ahmad Tohari. The data is then analyzed using the "distribution method" with the "direct element division" (BUL) technique, followed by the binary opposition technique. The results of the data analysis generally show that the types of meaning opposition that appear in the text of the first novel of the Ronggeng Dukuh Paruk trilogy include absolute opposition, polar opposition, relational opposition, hierarchical opposition, and compound opposition. Polar opposition is the most frequently used type of meaning opposition by the author, as the author often portrays the complexity of the characters' lives in a gradational manner. Abstrak Penelitian ini merupakan jenis penelitian deskriptif kualitatif yang menggunakan metode simak dengan teknik catat dalam mengumpulkan datanya. Penelitian ini bertujuan mendeskripsikan aspek leksikal antonimi dalam novel trilogi bagian pertama Ronggeng Dukuh Paruk “ Catatan Buat Emak” karya Ahmad Tohari yang diterbitkan pada tahun 1982. Objek penelitian ini adalah antonimi (oposisi makna). Data penenlitian ini berupa tuturan atau dialog antartokoh dalam novel  ronggeng dukuh paruk yang didalamnya terdapat oposisi makna beserta konteksnya. Sumber data penelitian ini adalah novel ronggeng dukuh paruk karya ahmad tohari. Data penelitian kemudian dianalisis menggunakan metode agih dengan teknik bagi unsur langsung (BUL) dengan teknik lanjutan oposisi dua-dua (binary oposition). Adapaun hasil analisis data secara umum menunjukkan bahwa oposisi makna yang muncul pada teks novel trilogi pertama Ronggeng Dukuh Paruk berupa oposisi mutlak, oposisi kutub, oposisi hubungan, oposisi hirarkial, dan oposisi majemuk. Oposisi kutub merupakan oposisi makna yang paling sering digunakan oleh pengarang karena pengarang sering menggambarkan kompleksitas kehidupan tokoh yang bersifat gradasi